Effect of CSR, Firm Size and Investment Decisions on Financial Performance: Consumer Non-Cyclicals Listed on IDX - Bunga Larasyati; Ahmad Rahbani Sulaiman Sirait (Universitas Pancasakti Tegal, 2026)
This study aims to examine the effect of Corporate Social Responsibility (CSR), firm size, and investment decisions on financial performance, with leverage as a control variable, in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. A quantitative approach was employed using multiple linear regression on secondary data obtained from annual reports and sustainability reports. The sample was determined through purposive sampling, yielding 30 consumer non-cyclicals companies listed on the Indonesia Stock Exchange during the 2021–2024 period, with a total of 120 observational data points. The results show that CSR and firm size each have a significant negative effect on financial performance, while investment decisions and leverage show no significant individual effect. Simultaneously, all four variables jointly affect financial performance, explaining 28.7% of the variation in ROA. This study indicates that CSR disclosure and asset scale instead exert negative pressure on profitability, while investment decisions have not been shown to make a significant individual contribution to improving financial performance in the short term.